Pelaksanaan Pengawasan Keimigrasian Terkait Kepatuhan Pelaporan Perubahan Alamat Orang Asing (Mimbar Keadilan, 2023)
The purpose of this study is to clarify the status of the implementation of immigration control related to the handling of foreign address change registration and to clarify the efforts and obstacles made by Immigration Class I TPI Tanjung Perak. Compliance with the registration of change of address for foreigners. Based on Article 71 (a) of Law no. 6/2011 which states that every foreigner who is in Indonesian territory is required to provide all information in the form of his/her identity and family and to report any change in civil status, citizenship, employment, guarantor, and change of address to the local Immigration Office. As for the role of immigration in monitoring the movement of foreigners entering and leaving Indonesian territory as well as the presence and activities of foreigners within Indonesian territory, repressive measures are required to apply administrative and criminal sanctions to support immigration enforcement. The method used in this research is normative-empirical research. The results of this study found that foreigners entering Indonesian territory must be accurately registered at the TPI immigration data center upon arrival and supervised in detecting the presence of foreigners in certain areas, thus ensuring complete foreigners with adequate documents. clarity. Obstacles or problems that arise in the implementation of immigration control, such as a lack of personnel to transfer information, duties, and functions of administrative and external supervision. The steps taken to explore these obstacles are expected to maximize the performance of licensed immigration officers in carrying out their immigration functions.